What can anarchism do for nursing? - Martin, Patrick (Nursing philosophy, 2023)
The notion of mutual aid, which Peter Kropotkin introduced in the 19th century, goes against the logic of competition as a natural condition, and instead shows how mutual aid is a more important factor to consider for the survival and flourishing of a group. The best cooperation strategies allow organisms to adapt to different types of changes in their environment—and we have witnessed a lot of these changes since the start of the COVID-19 pandemic. This propensity towards cooperation is not a foreign concept, despite how it seems to be overshadowed by individualism in Western societies. These reflections then lead us to believe it is possible to apply the anarchist philosophical principle of mutual aid to our social organizations, rather than giving priority, again and again, to competition and professional hierarchies, especially in healthcare systems, and particularly in hospitals were the majority of nurses work. For us, anarchist philosophical precepts, including but not limited to mutual aid, can be the key to a more adequate functioning of healthcare institutions. Anarchism can help to imagine the first steps needed to take to gradually move away from ideologies that encourage competition, professional hierarchies, and illegitimate authority. In this paper, we will first explore some anarchist philosophical precepts before turning to mutual aid as it is currently conceptualised, then highlight several concrete ways it is visible in nursing, as well as ways it can be applied in hospitals, and healthcare systems.